ANALISA PENGUJIAN KEKUATAN MATERIAL TROLI PADA SEPEDA BERBAHAN GALVANIS - dito yusuf akbar dito yusuf akbar; Rodika Rodika; Yudi Oktriadi (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2021)
Along with the development of increasingly advanced technology, the need to facilitate human activities is increasing. Many tools are created to facilitate human activities. Especially work that is heavy and dangerous when humans do it. One of them is the trolley as a tool for transporting goods. The tool in the form of a trolley has a main frame which is the place to be placed for loading. The material used in the main frame of the trolley is hollow galvanized with a size of 20x20x1.5mm. In this study, the analysis and calculation of frame strength using Solidworks software, with a static simulation feature so that the value of the stress that occurs can be known. Based on the results of the test, the maximum stress on the frame is 158,800,000N / m², the deflection is 4533mm, so it is concluded that the trolley frame that uses a hollow galvanized material (Hollow Galvanize) can be said to be able to withstand a load of 30kg, and it is known that trolleys can be used to help transport shopping goods. and bicycles can function according to design.